Eksperimen Pembelajaran Matematika Melalui Model Pembelajaran Partners In Learning Dan Problem Based Learning Ditinjau Dari Minat Belajar Siswa Kelas X Semester Genap Di Smk Muhammadiyah 1 SukoharjoTahun Ajaran 2014/2015 - Kusumaningsih, Andri, Dra. Sri Sutarni, M.Pd (2015)
This study aims to determine the differences in each category model of learning, interest in studying mathematics and its interaction with mathematics student learning outcomes. This research is quantitative. This study population is students of class X SMK Muhammadiyah 1 Sukoharjo academic year 2014/2015. Sempel retrieval is done by cluster random sampling technique. The sample was 32 students of class X TKR 3 subject teaching methods Partners In Learning as an experimental group and 31 students of class X TKR 2 subject teaching methods Problem Based Learning as a control group. Before treatment to test the balance. Data collection techniques with methods of questionnaires, tests and documentation. Test instrument covering validity and reliability test. Prerequisite test including normality test using Lilliefors and homogeneity test using Bartlett method. Test the hypothesis using two ways variance analysis with different cells. Based on hypothesis testing, we concluded that: (1) learning model Problem Based Learning mathematics learning outcomes better than learning model Partners In Learning. (2) There is no effect on the results of student interest in learning mathematics. (3) There is no interaction between learning models Partners In Learning and Problem Based Learning and learning interest of students towards mathematics student learning outcomes.